Using Ho Chi Minh’s People’s War and All-People’s National Defense Thoughts to Form Vietnam’s Military and National Defense Strategies - TRAN, Mong Nghi; CAO, Ngoc Bau (Journal of Ecohumanism, 2024)
This study analyzes the utilization of Ho Chi Minh’s ideas on people’s war and all-people’s national defense in the development of Vietnam’s National Defense Strategy and Military Strategy in the present day. The study highlights the significant theoretical and practical importance of Ho Chi Minh’s ideology, which is a useful resource for the Party, people, and military forces in protecting the socialist Vietnamese country. The paper emphasizes the necessity of acquiring a thorough comprehension of Ho Chi Minh’s ideologies, their fundamental principles, and the significance of innovatively implementing them in the formulation of defense and military strategies, in accordance with the Party’s directives, policies, and the unique conditions of the nation. Furthermore, it emphasizes the imperative of safeguarding and enhancing Ho Chi Minh’s revolutionary philosophy during the formulation of these policies. The research highlights the vital significance of Ho Chi Minh’s ideas in tackling important matters concerning national defense, military matters, and the readiness for possible wars or armed conflicts, while maintaining alignment with Vietnam’s talents and resources. The primary objective of the study is to provide a meaningful contribution to the preservation and progress of Ho Chi Minh’s intellectual legacy in the pursuit of establishing a robust national defense and military strategy for Vietnam.